Let

$\displaystyle S\ =$ {solar systems in the Milky Way galaxy}

$\displaystyle P\ =$ {planets}

$\displaystyle M\ =$ {moons}

The astronomer’s assertion is

$\displaystyle (\forall\,x\in S)(\exists\,y\in P)$ $\displaystyle (y$ is in $\displaystyle x$ and $\displaystyle (\forall\,z\in M)(z$ revolves around $\displaystyle y\ \rightarrow\ z$ has life forms))

If you negate it, it becomes

$\displaystyle (\exists\,x\in S)(\forall\,y\in P)$ $\displaystyle (y$ is in $\displaystyle x\ \rightarrow\ (\exists\,z\in M)(z$ revolves around $\displaystyle y$ and $\displaystyle z$ has no life forms))

Can you translate that into non-mathematical English? (Wink)